2019
DOI: 10.1007/s10433-019-00506-0
|View full text |Cite
|
Sign up to set email alerts
|

A critical review and development of a conceptual model of exclusion from social relations for older people

Abstract: Social exclusion is complex and dynamic, and it leads to the non-realization of social, economic, political or cultural rights or participation within a society. This critical review takes stock of the literature on exclusion of social relations. Social relations are defined as comprising social resources, social connections and social networks. An evidence review group undertook a critical review which integrates, interprets and synthesizes information across studies to develop a conceptual model of exclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 130 publications
(146 reference statements)
4
70
0
Order By: Relevance
“…Old age social exclusion involves multiple disadvantages that are derived from various factors including ageism, low socioeconomic status, declined social network, poor health, and urbanization ( Ellwardt et al, 2014 ; Fokkema et al, 2012 ; Tavernier & Aartsen, 2019 ; Walsh et al, 2017 ). Studies have shown that poor socioeconomic status significantly influences old age poverty, which, in turn, limits opportunities for travel, social participation, and interaction (e.g., Burholt et al, 2020 ; Chen et al, 2015 ). Negative life events, such as spousal bereavement, also significantly worsen the experience of social exclusion, including feelings of isolation and loneliness ( Cavalli & Bickel, 2007 ; MacLeod et al, 2019 ).…”
mentioning
confidence: 99%
“…Old age social exclusion involves multiple disadvantages that are derived from various factors including ageism, low socioeconomic status, declined social network, poor health, and urbanization ( Ellwardt et al, 2014 ; Fokkema et al, 2012 ; Tavernier & Aartsen, 2019 ; Walsh et al, 2017 ). Studies have shown that poor socioeconomic status significantly influences old age poverty, which, in turn, limits opportunities for travel, social participation, and interaction (e.g., Burholt et al, 2020 ; Chen et al, 2015 ). Negative life events, such as spousal bereavement, also significantly worsen the experience of social exclusion, including feelings of isolation and loneliness ( Cavalli & Bickel, 2007 ; MacLeod et al, 2019 ).…”
mentioning
confidence: 99%
“…6). Drawing on a new conceptual model of exclusion from social relations (Burholt et al 2019), they identify a range of personal attributes and life experiences associated with this form of exclusion and highlight its impacts on older people's health, well-being and sense of belonging. The conceptual model is grounded in a dynamic, life-course perspective that recognises the ways in which exclusion from social relations varies according to time and place, social norms, cultural values and policies and, hence, across societies.…”
Section: Domains Of Social Exclusionmentioning
confidence: 99%
“…Usually, material resources are measured via indicators related to income or wealth, while social relations are measured via indicators of social contacts and social participation. Here we consider a more nuanced approach, on the one hand taking a comprehensive measure of material deprivation [also see Ogg and Myck, and Sumil-Laanemaa et al this volume] and on the other using loneliness as a reflection, or outcome of exclusion from social relations (Burholt et al 2019; see also Burholt and Aartsen, and Morgan et al this volume). Based on longitudinal data from the Survey of Health, Ageing and Retirement in Europe (SHARE), the aim of this chapter is to examine the dynamics of loneliness and to investigate the causal relationship between material resources and loneliness.…”
Section: Introductionmentioning
confidence: 99%